Il cambiamento delle culture politiche in Italia: note per un programma di ricerca - Floridia, Antonio (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The paper proposes, in a non-systematic ways, a discussion of some issues that may be the subject of a new phase of research on the subject of political culture in Italy. First, it addressed the issueof the persistence of territorial differentiation of the political culture in Italy: are still valid those interpretative categories that featured a long period of studies on this issue? The interplay between general and nifying trends and persistence of a territorial political culture is then analyzed, taking as an example the case of the electoral success of the Five Star Movement. Finally, it discusses the transformation of the political culture in Tuscany, one of the “red regions” where the ideal-typical model of “territorial political subculture” has emerged historically in a form almost “pure”. Is this model still valid? and what are the changes that have occurred?